2015
DOI: 10.1007/s00382-015-2777-9
|View full text |Cite
|
Sign up to set email alerts
|

Can we trust climate models to realistically represent severe European windstorms?

Abstract: times, and horizontal and vertical resolutions. These runs are then compared to re-analysis data. The main conclusions from this work are: (a) objectively identified cyclone tracks are represented satisfactorily by most hindcasts; (b) sensitivity to vertical resolution is low; (c) cyclone depth is systematically under-predicted for a coarse resolution of T63 by both climate models; (d) no systematic bias is found for the higher resolution of T127 out to about three days, demonstrating that climate models are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 66 publications
1
21
2
Order By: Relevance
“…Averaged over all 39 storms, the deterministic forecasts are 2.4 hPa, −0.2° latitude and −0.5° longitude different from the analysis at 24 h lead time. These results are consistent with the work of Froude et al (), who examined a larger set of storms including many weak storms.The results from Trzeciak et al () also indicate that storm intensity is generally underpredicted, with a strong dependence on model resolution.…”
Section: Analysis Of Storm Forecastsmentioning
confidence: 94%
See 3 more Smart Citations
“…Averaged over all 39 storms, the deterministic forecasts are 2.4 hPa, −0.2° latitude and −0.5° longitude different from the analysis at 24 h lead time. These results are consistent with the work of Froude et al (), who examined a larger set of storms including many weak storms.The results from Trzeciak et al () also indicate that storm intensity is generally underpredicted, with a strong dependence on model resolution.…”
Section: Analysis Of Storm Forecastsmentioning
confidence: 94%
“…The storms were tracked using the method described in detail by Trzeciak et al (). The first steps are to identify a minimum in mean sea‐level pressure (MSLP) and an associated maximum in the vorticity at 850 hPa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both van Oldenborgh et al (2015) and Wild et al (2015) use observational analysis to challenge the suggestion (e.g., Huntingford et al, 2014) that the PREPUBLICATION COPY intense storminess over the UK in winter 2013/2014 was driven by anomalously warm Pacific SSTs, which might have an anthropogenic component. Trzeciak et al (2014) suggest that although current global climate models generally under-represent the intensity of extratropical cyclones due to insufficient latent heat release, once the horizontal resolution is finer than about 100 km they should be adequate, and that the systematic biases will then mainly involve storm track location. Seiler and Zwiers (2015b) found that resolution is not correlated with explosive storm intensity across the CMIP5 ensemble, but note that competing effects of vertical resolution and model physics inhibit strong interpretation of that result.…”
Section: Prior Knowledge and Overview Of Attribution Studiesmentioning
confidence: 99%